2018
DOI: 10.1080/21645515.2018.1496770
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged effect of allergen sublingual immunotherapy to grass pollen

Abstract: A prolonged positive effect after AIT to grass pollen was observed in elderly patients with allergic rhinitis. Further trials are needed to confirm this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Levels of cypress-specific IgE tended to increase in certain subjects (although not statistically significant). Moreover, in certain subjects levels of cypress-specific IgG4 [25,27,[36][37][38], the decoy or inhibitor of cypress-specific IgE against cypress pollen, decreased after the beginning of pollen dispersal. is represents a reversal of the changes observed for cypress-specific IgE.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of cypress-specific IgE tended to increase in certain subjects (although not statistically significant). Moreover, in certain subjects levels of cypress-specific IgG4 [25,27,[36][37][38], the decoy or inhibitor of cypress-specific IgE against cypress pollen, decreased after the beginning of pollen dispersal. is represents a reversal of the changes observed for cypress-specific IgE.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an ongoing study of the long-term effects of SLIT on allergies to grasses and mites showed sustained efficacy up to 5 years following discontinuation of AIT treatment [ 33 , 34 ]. These observations also confirmed an increase in IgG4 titer for desensitized allergens, which demonstrates the flexibility of the immune system in old age.…”
Section: The Long-term Effect After Allergen Immunotherapy In Seniorsmentioning
confidence: 99%